Peranan Pengadilan Tata Usaha Negara Dalam Penyelesaian Sengketa Merek - Muhammad Anwar Ibrahim; Gema Permana Rahman; Taufiqurrohman Syahuri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
As time goes by and the development of law in Indonesia, the trademark has become a symbol that has been integrated in the life of society. Given the importance of a brand, the brand must get a protection from each country. Protection of a trademark in Indonesia is regulated in Act No. 20 Year 2016 on Trademarks and Geographical Indications, one of the materials regulated in the Act is about the settlement of trademark disputes. The settlement of trademark disputes is resolved by two judicial bodies, namely the Commercial Court and the State Administrative Court. This research uses a normative juridical approach method with descriptive analytical analysis of legal materials. The results of this study found that the authority of the State Administrative Court (PTUN) is to examine, decide and resolve State Administrative disputes (TUN) in a dispute arising in the field of State Administrative law (TUN) between persons or civil law entities (members of the public) with agencies or TUN officials (government) within the scope of the central government also includes local government as a result of the issuance of a TUN decision (beschikking). State Administrative Court has a very important role in resolving trademark disputes on the basis of registered trademark owners object to the decision to remove the registered trademark on the initiative of the Minister.